Produktivitas Primer Fitoplankton pada Berbagai Periode Cahaya di Perairan Teluk Kao, Kabupaten Halmahera Utara - Yuliana Yuliana (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The objective of this research was to know the phytoplankton primary productivity on light periodicities in Kao Bay. The research was conducted from November 2004 to February 2005 in Kao Bay, North Halmahera district. The primary productivity was measured at one station with 4 depths of 0, 5, 10, and 15 m. The oxygen contains in light and dark bottles converted to carbon production were used to measure the primary productivity. The light and dark bottles were incubated in 3 light periodicities, i.e. I (06.00-10.00 am), II (10.00 am-14.00 pm), and III (14.00-18.00 pm), and environmental parameter also measured, namely temperature, salinity, pH, nitrate, orthophosphate, and silicate concentration. The results showed that primary productivity (mgC/m3/hour) range from 60.051 to 341.599, the highest was occurred in II (1076.737) and lowest in I (666.342). The environmental parameters were temperature 30.8-32.20C, salinity 34-36‰, pH 7.62-7.77, nitrate 0.083-0.207 mg/l, orthophosphate 0.009-0.370 mg/l, and silicate 0.000-0.008 mg/l. There were 3 classes of phytoplankton: Bacillariophyceae (14 genera), Cyanophyceae (1 genera), and Dinophyceae (3 genera). It could be concluded that light period has significant influence on phytoplankton primary productivity.